PROLIFERATIVE AND SECRETORY RESPONSE OF MONONUCLEAR LEUCOCYTES TO COMBINED INFLUENCE OF ETHAMBUTOL AND MYCOBACTERIAL ANTIGENE - V. A. Serebryakova; O. A. Vasil'eva; O. I. Urazova; V. V. Novitsky; O. V. Voronkova; A. K. Strelis; T. E. Budkina; R. R. Hasanova; I. O. Naslednikova (Медицинская иммунология)
Abstract. The article deals with results of studying combined effects of ethambutol and protein antigen of Мycobacterium tuberculosis upon proliferative response and cytokine-producing ability of peripheral blood mononuclear cells in patients with infiltrative lung tuberculosis prior to beginning of specific antibacterial therapy. The mononuclear blood cells were cultivated with complex protein antigen of Мycobacterium tuberculosis and ethambutol. In the patients with lung tuberculosis, a decrease in proliferative reserve of lymphocytes was detected, in absence of increased IL-2 and IL-10 secretion. The combined effect of ethambutol and protein antigen of Мycobacterium tuberculosis upon peripheral blood mononuclear cells in the patients with pulmonary tuberculosis and healthy donors was similar, and it was expressed as antiproliferative effect and selective suppression of IFNγ production.